EFFECT OF KIESELGUHR FILTRATION ON OPTICAL PROPERTIES OF BEER - Helena Frančáková (Journal of Microbiology, Biotechnology and Food Sciences, 2013)
Looks of beer is an important factor which is associated with high clarity. Clarity of beer is a basic precondition of its good marketability and consumer satisfaction. Beer filtration is ideal tool to create required optical properties. There is a high accent on this operation in brewery and minibrewery. The process of filtering removes unwanted haze-active substances in order to increase clarity and overall stability of beer. Objective method to expressing clarity of beer is nephelometric determination of turbidity, which is highly sensitive and achieved by reliable results directly in the units used to express the turbidity values in beer. The objective of our study was to measure haze before and after filtration in various types of beer with different length of lagering. Kieselguhr was used as filtration material. Haze of beer was measured by haze meter in determination under 2 angles and values were expressed in European Brewery Convention units directly.